What Helps and What Hinders? Exploring the Role of Workplace Characteristics for Parental Leave Use and Its Career Consequences - Claire Samtleben; Julia Bringmann; Mareike Bünning; Lena Hipp (Social Sciences, 2019)
The division of parental leave among couples today is still unequal—even in countries with progressive leave schemes. Given the gendered nature of the workplace, we examine how organizational characteristics relate to fathers' uptake and length of parental leave as well as to the perceived career consequences of leave uptake among those fathers who took leave. In our mixed methods study, we draw on unique quantitative and qualitative data on different-sex couples with young children in Germany (2015). We find that the fear of professional repercussions and the lack of a replacement at work inhibit fathers both from taking leave in general and, for those who take leave, from taking it for more than two months. Interestingly, however, the majority of fathers who took leave did not think that their leave negatively affected their professional advancement. This positive evaluation was independent of the length of leave. We compared fathers' perceived leave consequences to those of mothers, who tended to have a more negative view of the impact of taking leave on their careers. Both fathers and mothers were more likely to report negative career consequences if they worked in organizations that promoted a strong ideal worker norm, that is, where employees thought that they were expected to prioritize paid work over their private life.
Keywords: 330; parental leave; employment; workplace culture; ideal worker norm; gender equality; mixed methods